Analysis of the Implementation of Foreign Surveillance Policy - Helistiawan, Anton; Tjenreng, Zubakhrum (Journal La Sociale, 2025)
Immigration policy is an integral part of governance that aims to maintain state sovereignty and public order. In the midst of the dynamics of globalization and increasingly intensive cross-border human mobility, Indonesia faces major challenges in implementing immigration policies effectively. This article aims to analyze the implementation of the Indonesian government's policies in the field of immigration, focusing on the surveillance of foreigners as a vital instrument in ensuring national security and public order. This paper uses a descriptive qualitative approach with the method of literature study and policy analysis, this article reveals that even though the legal and institutional framework has been formed, policy implementation still faces various challenges such as inter-agency coordination, human resource capacity, and the use of information technology. These findings show the need to strengthen policy integration, synergy between actors, and digitize the immigration surveillance system. Policy recommendations are focused on institutional capacity building, immigration digital reform, and strengthening multi-stakeholder collaboration.